Pengaruh Model Pembelajaran Guide Inquiry Terhadap Hasil Belajar Matematika Materi Bangun Ruang di Kelas V MI - Fauzi, Akhmad; Rahmawati, Rika; Agustyarini, Yhasinta; Nurhayati, Uci (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
Mathematics has an important role in the world of education, but education in Indonesia in mathematics cannot be said to be good. This is in accordance with the PISA 2022 results that Indonesia has experienced an increase in ranking by 5-6 positions but is still at the bottom of other countries in mathematics ability. Learning mathematics is still considered difficult and unpleasant by students, causing low learning outcomes. Using the guided inquiry learning model could be a solution because it can attract students and better understand students' understanding of learning concepts. The main aim of this research is to determine the effect of the guided inquiry learning model on student learning outcomes. This research uses a quantitative pre-experimental design approach in the form of one group pretest & posttest. The research sample was 21 students. The data collection technique in this research used a written test. The results of the data analysis that had been carried out showed that the average value before treatment was given was 33.33 Meanwhile, the average after the treatment was given was 67.52. The paired sample t test results obtained were Sig. (2-tailed) of 0.000 < 0.05 So it can be concluded that the guided inquiry learning model has an effect on student learning outcomes